MiYoga: a randomised controlled trial of a mindfulness movement programme based on hatha yoga principles for children with cerebral palsy: a study protocol. Issue 7 (10th July 2017) - Mak, Catherine; Whittingham, Koa; Cunnington, Ross; Boyd, Roslyn N
Abstract : Introduction: Cerebral palsy (CP) is the most common childhood physical disability, with life-long impacts for 1.77 in 1000 children. Although CP is primarily a physical disability, children with CP have an increased risk of experiencing cognitive difficulties, particularly attention and executive function deficits. Impairment in cognitive abilities can lead to subsequent impairment in independent functioning, education, employment and interpersonal relationships. This paper reports the protocol of a randomised controlled trial of a novel family-centred lifestyle intervention based on mindfulness and hatha yoga principles (MiYoga). MiYoga aims to enhance child and parent outcomes for children with CP. Methods and analysis: The aim is to recruit 36 child-parent dyads (children aged 6–16 years; bilateral or unilateral CP; Gross Motor Function Classification System I–III), who will be randomly assigned to two groups: MiYoga and wait list control. The MiYoga programme will be facilitated in a group format for 8 weeks. Assessments will be administered at baseline, prior to MiYoga, following completion of MiYoga, and at 6-month follow-up (retention). The primary outcome will be the child's sustained attentional ability as measured by the Conner's Continuous Performance Test II. Other outcomes of interest for children with CP consists of attentional control, physical functioning, behavioural and well-being. For parents, the outcomes of interest are mindfulness, psychological flexibility and well-being. Data will be analysed using general linear models, specifically analysis of covariance and analysis of variance. Ethics and dissemination: Full ethical approval for this study has been obtained by the Children's Health Queensland Hospital and Health Service Research Ethics Committee (HREC/12/QRCH/120) and The University of Queensland (2012000993). If MiYoga is proven effective, its dissemination would assist children with CP and complement their ongoing therapy by improving the ability of the child to pay attention at school and in therapy, and alleviating environmental stressors for both the child and his/her parents. Trial registration number: ACTRN12613000729729; Pre-results.http://www.ANZCTR.org.au/ACTRN12613000729729.aspx Date of trial registration: Prospectively registered on 2 July 2013–present (ongoing). Findings to date: Recruitment is complete. Data are still being collected at present. We aim to complete data collection by February 2017.